2010
DOI: 10.1152/ajprenal.00487.2009
|View full text |Cite
|
Sign up to set email alerts
|

In vivo renal arginine release is impaired throughout development of chronic kidney disease

Abstract: The kidney is a major site of arginine synthesis where citrulline is converted to arginine via argininosuccinate synthase (ASS) and lyase (ASL). The rate-limiting step in arginine synthesis by the normal kidney is the rate of citrulline delivery and uptake to the renal cortex. We tested whether with chronic kidney disease (CKD) renal arginine synthesis may be compromised. Using the 5/6 renal ablation/infarction (A/I) injury model, we measured renal citrulline delivery and uptake as well as arginine release at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 36 publications
3
31
1
1
Order By: Relevance
“…In addition, the relative presence of arginine compared with citrulline (Arg/Cit) was progressively lower in more advanced CKD stages, suggesting a lower activity of argininosuccinate synthase (Enzyme Commission [EC] number 6.3.4.5) and/or argininosuccinate lyase (EC4.3.2.1). In an animal model, CKD induced a reduction in the renal uptake of citrulline in the abundance of these enzymes (14). We also found that reduced kidney function was associated with a greater urinary citrulline excretion, confirming that increased citrullinemia was not related to retention but rather, had a metabolic origin.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, the relative presence of arginine compared with citrulline (Arg/Cit) was progressively lower in more advanced CKD stages, suggesting a lower activity of argininosuccinate synthase (Enzyme Commission [EC] number 6.3.4.5) and/or argininosuccinate lyase (EC4.3.2.1). In an animal model, CKD induced a reduction in the renal uptake of citrulline in the abundance of these enzymes (14). We also found that reduced kidney function was associated with a greater urinary citrulline excretion, confirming that increased citrullinemia was not related to retention but rather, had a metabolic origin.…”
Section: Discussionsupporting
confidence: 68%
“…Animals were kept for 8 wk after surgery and were monitored for the development of kidney disease. This time frame is sufficient for animals to develop moderate to severe kidney disease (11), endothelial dysfunction, glomerulosclerosis, and decreased cardiac function (30,33), confirming the development of both CKD and CVD in this model. Renal function was assessed in all groups by measuring urine protein excretion, serum creatinine, and blood urea nitrogen (BUN).…”
Section: Methodssupporting
confidence: 60%
“…This has been referred to as the "L-arginine paradox" and suggests that NO is derived from extracellular sources of L-arginine (34,47). Classified as a semiessential amino acid, the body is normally capable of producing sufficient quantities of L-arginine to sustain homeostasis (40); however, the synthesis of L-arginine occurs primarily in the kidneys and is impaired in CKD (6,11). Supplementation with exogenous L-arginine would therefore be highly beneficial to patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis for ASS and ASL in kidney cortex was described previously [3], as were DDAH isoforms, SOD isoforms and p22phox Western blot techniques [10]. For arginase, rabbit polyclonal arginase II antibody (Santa Cruz, 1:3,000) with goat anti-rabbit IgG-HRP secondary (Bio-Rad, 1:3,000).…”
Section: Methodsmentioning
confidence: 99%
“…There are multiple potential causes of NO deficiency in CKD, including reduction in the NO synthase (NOS) substrate, L -arginine ( L -Arg) [1] since the normal kidney synthesizes most of the circulating L -Arg; this is by enzymatic conversion of citrulline by argininosuccinate synthase (ASS) and lyase (ASL) [2]. We recently reported impaired renal release of L -Arg in renal mass reduction (RMR)-induced CKD [3]. L -Arg is made in proximal tubules and secreted into plasma via transporters including the cationic amino acid transporter (CAT)1 [4].…”
Section: Introductionmentioning
confidence: 99%